Effect of immune responses on breath methane dynamics - Polag, Daniela; Keppler, Frank (Journal of breath research, 2023)
Methane (CH4) which can be detected in human breath has long been exclusively associated with anaerobic microbial activity (methanogenesis) in the gastrointestinal tract. However, recent studies challenge this understanding by revealing that CH4 might also be produced endogenously in cells through oxidative-reductive stress reactions. Consequently, variations in breath CH4 levels compared to an individual’s baseline level might indicate enhanced oxidative stress levels, and, therefore, monitoring breath CH4 levels might offer great potential for ‘in vivo’ diagnostics such as disease diagnosis, monitoring the efficacy of treatments, or during the application of personalized medicine. To evaluate the effects from immune responses triggered by infections, inflammations, and induced perturbation by vaccination on CH4 dynamics in breath, two subjects were monitored over a period of almost 2 years. Breath CH4 levels were measured by gas chromatography equipped with a flame-ionization detector. Both subjects exhibited significant deviations (positive and negative, respectively) from their normal CH4 breath levels during periods of potential enhanced immune activity. Deviations from the ‘healthy state’ were indicated by the exceeding of individual CH4 ranges. Moreover, for the first time we could clearly prove CH4 degradation induced through vaccination by measuring stable carbon isotopes of CH4 using gas chromatograph-combustion-isotope ratio mass spectrometry. Hence, breath CH4 concentration and isotopic analyses may be used as a biomarker to evaluate specific immune responses and individual immune states.
Veröffentlicht: 3. August 2023
Gesehen am 25.09.2023